(Invited) Rapid In-Situ Carbon and Oxygen Cleaning of In0.53Ga0.47As(001) and Si0.5Ge0.5(110) Surfaces via a H2 RF Downstream Plasma. (4th May 2016) - Wolf, Steven; Edmonds, Mary; Jiang, Ximan; Droopad, Ravi; Yoshida, Naomi; Dong, Lin; Galatage, Rohit; Siddiqui, Shariq; Sahu, Bhagawan; Kummel, Andrew
Abstract : The In0.53 Ga0.47 As(001) and Si0.5 Ge0.5 (110) surfaces were cleaned using a downstream RF plasma. On the air-exposed In0.53 Ga0.47 As(001) surface, a 2 second 100 millitorr H2 plasma dose fully removed carbon and oxygen. On the ex-situ wet cleaned Si0.5 Ge0.5 (110) surface, nearly all carbon and oxygen are removed via a 2 second exposure of 5% H2 in Ar plasma. To prevent oxygen deposition from the plasma tube while maximizing the atomic H flux, for Si0.5 Ge0.5 (110), the plasma power, pressure, and gas composition must be controlled. The Si0.5 Ge0.5 (110) surface is more sensitive than the In0.53 Ga0.47 As(001) surface to trace oxygen in the plasma stream consistent with the higher heat of formation per Si of SiO2 than the heat of formation per Ga of Ga2 O3 . The higher heat of formation of SiO2 is expected to both increase oxygen adsorption and prevent the atomic H from forming volatile products with SiO2 on Si0.5 Ge0.5 (110), in contrast to In0.53 Ga0.47 As(001).